15. READINESS OF THE HEALTHCARE SYSTEM FOR SCREENING, DIAGNOSING, AND SUPPORTING THE TREATMENT OF HEARING LOSS FOR THE OLDER ADULTS IN THE HUE CITY (Vietnam Journal of Community Medicine, 2024)
Objective: Assessing the readiness of the healthcare system for screening, diagnosing, and supporting the treatment of hearing loss for the older adults in Hue city, Vietnam.Subjects and Research Methods: A mixed-methods study was conducted with representatives of 15 healthcare facilities in Hue City. A portion of the Service Availability and Readiness Assessment (SARA) toolkit was used. In-depth interviews were conducted with the study participants to further evaluate the advantages and challenges in screening, diagnosing, and supporting treatment.Results: Most community health centers are not ready for screening, diagnosing, and supporting treatment. The main obstacles are the lack of guidelines, untrained healthcare staff, and insufficient equipment. Public hospitals/health centers have trained healthcare staff and guidelines, but the guidelines are not standardized, half of the units lack pure-tone audiometers, and only one facility is capable of providing support treatment.Conclusion: There is a need to enhance the capacity of healthcare facilities to meet the increasing issue of hearing loss in the older adults.
Keywords: Hearing loss; older adults; healthcare system readiness